GROWTH RESPONSE OF LABEO ROHITA FINGERLINGS FED WITH DIFFERENT FEEDING REGIMES UNDER INTENSIVE REARING - M. Abid; M. S. Ahmed (Journal of Animal and Plant Sciences, 2009)
Feeding trials were conducted to determine the efficacy of varying dietary protein regimes on growth of Labeo rohita fingerlings under intensive rearing for a period of six months. Stocking density was 25fish/glass aquarium m-2 (280 liter water volume). Seven different diets were tested. Out of seven diets, three low cost based diets having (35%, 40% and 45% crude protein) and three high cost based diets having (35%, 40% and 45% crude protein) were evaluated against a control (rice polish) having (12% crude protein) in triplicate glass aquaria. Fish were fed daily @ 4% of wet body weight twice a day. Mean body weight gain, mean length gain, specific growth rate, feed conversion ratio and survival rate were evaluated to determine the growth performance in different treatments. The survival rate was 100 % at all feeding levels. In aquaria fish fingerlings fed with 45% low cost based diet showed significantly higher (P<0.05) weight gain (26.17g) than other diets and highly significant to control diet (9.77g.) Water quality variables such as temperature, dissolved oxygen, total hardness, etc. were found approximately constant for rapid growth and survival for Labeo rohita fingerlings.
Keywords: Feed conversion ratio; freshwater fish; fingerlings; Labeo rohita; stocking density; survival rate